Response of cracked simply supported concrete beam with moving vehicle load - Zhou, Linyun; Liu, Huangin (Structural concrete : journal of the FIB, 2016)
The dynamic response of a cracked beam subjected to moving loads has been studied extensively in the past decades. However, very little is known about the dynamic impact factors and crack propagation when vehicles move along the cracked beam. It can be reasonably postulated that a crack extension may occur when the vehicle loads cross the cracked bridge at a high speed. As a result, the dynamic response will be enlarged significantly due to the flexural rigidity reduction induced by cracks, which may result in a dangerous effect on structures. To address this problem, a three‐dimensional vehicle‐bridge model was developed to investigate the dynamic response of cracked bridges with crack breathing. Crack breathing is simulated at the crack surface using contact elements. The modified crack closure method is adopted to calculate the stress intensity factors. The results showed that the impact factors for the damaged bridge under a moving load could be notably larger than those for the intact bridge, and could exceed the value specified in the AASHTO bridge design code. Meanwhile, crack propagation may occur when the vehicles move along the cracked bridge at a high speed. So, it is very necessary to limit the velocity and transverse position of the vehicles to avoid further damage to the cracked bridge.